2019
DOI: 10.1002/adsc.201900691
|View full text |Cite
|
Sign up to set email alerts
|

Silver‐Catalyzed Radical Cascade Cyclization of Unactivated Alkenes towards Cyclopenta[c]quinolines

Abstract: A convenient radical cascade cyclization of aniline-linked 1,7-enynes with 1,3-dicarbonyl compounds was developed to synthesize cyclopenta [c]quinolines in the presence of AgNO 3 /K 2 S 2 O 8 . A wide range of cyclopenta[c]quinolines were prepared in moderate to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…[51a-f] Recently, the Yu group developed an efficient protocol to construct various cyclopenta[c] quinolines through silver-catalyzed tandem radical annulation of aniline-linked 1,7enynes with 1,3-dicarbonyl compounds without any halogenated reactants (Scheme 33). [52] The amount of oxidant was found to be closely related to the product yield, and further evaluations indicated that 3.0 equivalents of the oxidant gave the best performance. Further explorations of the substrate scope revealed that both cyclic and acyclic 1,3-dicarbonyl compounds were suitable for this transformation, while the dicarbonyl substrates such as diethyl malonate failed to convert to the cyclization products.…”
Section: Radical Cyclization Reactionmentioning
confidence: 93%
See 1 more Smart Citation
“…[51a-f] Recently, the Yu group developed an efficient protocol to construct various cyclopenta[c] quinolines through silver-catalyzed tandem radical annulation of aniline-linked 1,7enynes with 1,3-dicarbonyl compounds without any halogenated reactants (Scheme 33). [52] The amount of oxidant was found to be closely related to the product yield, and further evaluations indicated that 3.0 equivalents of the oxidant gave the best performance. Further explorations of the substrate scope revealed that both cyclic and acyclic 1,3-dicarbonyl compounds were suitable for this transformation, while the dicarbonyl substrates such as diethyl malonate failed to convert to the cyclization products.…”
Section: Radical Cyclization Reactionmentioning
confidence: 93%
“…In general, multiple steps or/and harsh reaction conditions are required for the construction of diverse cyclopenta[ c ]quinoline scaffolds which greatly restrict the further applications . Recently, the Yu group developed an efficient protocol to construct various cyclopenta[ c ] quinolines through silver‐catalyzed tandem radical annulation of aniline‐linked 1,7‐enynes with 1,3‐dicarbonyl compounds without any halogenated reactants (Scheme ) . The amount of oxidant was found to be closely related to the product yield, and further evaluations indicated that 3.0 equivalents of the oxidant gave the best performance.…”
Section: Cyclization Reactionmentioning
confidence: 99%
“…Similarly, potassium persulfate (K 2 S 2 O 8 ) as an inexpensive and easily available inorganic oxidant has been widely used in oxidative transformations . In 2018, Tang and Chang's group reported a practical and efficient method for selective intramolecular radical trifluoromethylacylation of alkenes 16 with inexpensive CF 3 SO 2 Na and K 2 S 2 O 8 to synthesize CF 3 ‐functionalized chroman‐4‐ones 17 (Scheme ) .…”
Section: Radical Strategies For the Synthesis Of 3‐substituted Chrmentioning
confidence: 99%
“…disclosed a novel methodology towards the synthesis of cyclopenta[ c ]quinolines 52 catalyzed by AgNO 3 /K 2 S 2 O 8 (Scheme 21). [32] A radical cascade cyclization approach of 1,3‐dicarbonyls 50 with aniline‐linked 1,7‐enynes 51 afforded the desired product in good yields. Electron‐rich moieties attached to aniline‐linked 1,7‐enynes provided better yields than electron‐deficient ones.…”
Section: Six Membered Heterocycles With One Heteroatommentioning
confidence: 99%